Effectiveness of UAN fertilisation with potassium thiosulphate in pepper and tomato cultivation - Marzena Błażewicz-Woźniak; Marzena Brodowska; Monika Karsznia (Acta Scientiarum Polonorum: Hortorum Cultus)
The European Commission proposed the European Green Deal, aiming to reduce plant nutrient losses by at least 50% while preventing soil fertility deterioration and reducing fertiliser use by at least 20% by 2030. Of particular importance for environmental reasons is the reduction of nitrogen fertilisation rates. UAN is a highly concentrated nitrogen fertiliser in an aqueous solution of nitrate and urea ammonium nitrate. This study evaluated the effectiveness of fertilisation in pepper and tomato cultivation using UAN mixtures with potassi um thiosulphate in proportions selected based on a model pot experiment. The field experiment was conducted from 2019 to 2020 at the Felin Experimental Farm of the University of Life Sciences in Lublin. The test plants were sweet peppers of the Balta F1 cultivar  (Capsicum annuum L.) and tomatoes of the Mirsini cultivar (Lycopersicon esculentum Mill.). The experiment included the following variable factors: nitrogen dose (2 levels: N1 – optimum nitrogen rate and N2 – nitrogen rate reduced by 25% from the optimum dose) and fertiliser composition (2 levels: pure UAN – N : K0 : S0, UAN with potassium thiosulphate – N : K1: S1). Taking into account the pepper yield and the accumulation of nitrogen, phosphorus, potassium and sulphur in the fruit, the most favourable fertilisation combination was the combination of an optimal nitrogen dose (170 kg N ha‒1) with potassium thiosulphate. The reduction of the nitrogen dose and the treatment of fertilisation with a dose of 128 kg N ha‒1 with potassium thiosulphate favoured an increase in the vitamin C content of the pepper fruit. The effect of nitrogen dose on tomato fruit yield was modified by the year of the study. Thus, in tomatoes, it is possible to reduce the nitrogen dose depending on weather conditions. At the same time, the addition of potassium thiosulphate is recommended, which has a beneficial effect on the fruit’s potassium, phosphorus and sulphur and vitamin C content. There was no significant effect of varying nitrogen and potassium fertilisation on the dry matter content of pepper and tomato fruit, while the effect on calcium, magnesium and extract content was inconclusive.